Habitat conditions of reef-forming corals directly affect the spatial distribution and stability in fish and macroinvertebrate communities: A case study of Mischief Reef - Peng Xu; Jianfeng Gan; Lintao Huang; Danping Xie; Feilong Li; Hui Huang (Ecological Informatics)
Environmental DNA (eDNA) metabarcoding is a powerful method for extracting species information from environmental samples, thereby supporting the establishment or enhancement of biodiversity assessments. We utilized eDNA baseline data from Mischief Reef to investigate changes in community structure and their underlying drivers within a small-scale habitat model. Our initial analysis identified 178 species of fish and macroinvertebrates (including crustaceans and mollusks) through eDNA. The communities were obviously divided into high (Hcrc) and low (Lcrc) coral reef cover groups, with coral cover of 19.5 % and 8.79 %, respectively. We found that taxonomic (TD) and phylogenetic (PD) diversities followed the order TDHcrc > TDLcrc and PDHcrc > PDLcrc respectively. However, no significant difference was observed in functional diversity (FD) between the two groups, implying that Lcrc maintains key organisms responsible for essential ecosystem functions. Nevertheless, the low functional redundancy of Lcrc indicates its relative vulnerability and poorer resistance to disturbances in the event of key functional organism loss. Furthermore, the co-occurrence network of Hcrc was more intricate than that of Lcrc, boasting a greater number of nodes and edges. In addition to Eupercaria, both Acanthuriformes and Ovalentaria played significant roles in the Hcrc ecological network, each representing over 10 %. Conversely, Perciformes and Holocentriformes were prominent in the Lcrc ecological network, with each constituting more than 10 %. Further, the neutral community models fit degree of both groups was low (R2 < 0.3), the fit degree of the Hcrc community (R2 = 0.222) was higher than that of the Lcrc community (R2 = 0.17), and the assemblies of the Hcrc and Lcrc communities were dominated by diffusion restriction (86.9 %) and ecological drift (72.8 %), respectively. Finally, our findings demonstrate strong interactions between the environment factors and biological communities, revealing that the coverage of reef-building coral is closely tied to surrounding biological resources. A stable sea surface seawater y velocity and a slight increase in seawater potential temperature were conducive to the survival of biological communities. Overall, we highlight that eDNA is a reliable tool for detecting differences in community structure across small-scale habitats and provides valuable insights into ecosystem functioning and resilience under varying coral reef conditions.